2021
DOI: 10.2174/0929867327666200228110738
|View full text |Cite
|
Sign up to set email alerts
|

The “Big Five” Phytochemicals Targeting Cancer Stem Cells: Curcumin, EGCG, Sulforaphane, Resveratrol and Genistein

Abstract: : Cancer stem cells (CSCs) constitute a subpopulation of tumor cells that possess self-renewal and tumor initiation capacity, and the ability to give rise to the heterogeneous lineages of cancer cells that comprise the tumor. CSCs exhibit intrinsic mechanisms of resistance to virtually all conventional cancer therapeutics, allowing them to survive current cancer therapies and to initiate tumor recurrence and metastasis. Different pathways and mechanisms that confer resistance and survival of CSCs, including ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…Moreover, cancer research has shown significant anti-CSC activities of plant-derived molecules against a wide variety of cancer types [ 69 ]. It is assumed that these activities are mediated through modulation of multiple cell mechanisms/signaling processes that demand an urgent need for in-depth evaluation within oncology research [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cancer research has shown significant anti-CSC activities of plant-derived molecules against a wide variety of cancer types [ 69 ]. It is assumed that these activities are mediated through modulation of multiple cell mechanisms/signaling processes that demand an urgent need for in-depth evaluation within oncology research [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…[283][284][285] Furthermore, genistein also inhibited stemness, which is closely related to the developmental pathways including Wnt/β-catenin and GDF15, in renal and other cancers. 283,286,287 Clinical trials of genistein in cancer therapy have been conducted, including in breast cancer (NCT00244933) (NCT00290758), in breast or endometrial cancer (NCT00099008), in bladder cancer (NCT00118040), and in prostate cancer (NCT00005827). However, clinical applications of genistein are still limited due to the poor solubility and bioavailability regardless of its potential anticancer activity by drug repurposing.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…Few derivatives of plant-based phytochemicals have gained prominence in the field of cancer biology because of their limited cytotoxic effects and high specificity. Among these bioactive compounds resveratrol, curcumin, quercetin, paclitexal, genistein, Epigallocatechin-3-gallate (EGCG) and several others have been investigated extensively for their antitumor properties [ 80 ]. Phytochemicals have limited side effects which make them safe for the administration as proven in animal models and cell lines.…”
Section: Natural Compounds As Possible Therapeutic Solutionmentioning
confidence: 99%